Unlocking the secrets of Modern mummies: an untapped resource in Northern Italian Museums - Pangrazzi, Caterina (Medicina Historica, 2023)
This letter expresses concerns regarding the lack of attention given to the mummies housed in museums in Northern Italy, which could provide valuable insights into health and disease patterns, cultural practices, and changing medical technologies during the modern era. The mummies represent a diverse range of cultural and socioeconomic backgrounds and time periods, from wealthy nobles to commoners from the 17th to the 20th centuries. Analysing or restudying these mummies could provide new insights into prevalent health conditions such as tuberculosis, syphilis, and other infectious diseases, as well as the impact of changing cultural practices and medical technologies. Furthermore, the study of these mummies could also provide valuable insights into the cultural practices surrounding death and burial during the modern era, including the use of mummification techniques among certain religious groups. The letter highlights the obstacles to this research, including lack of funding and ethical concerns surrounding the study of human remains. Nonetheless, the potential benefits of restudying these mummies are too significant to ignore, and the scientific community is urged to recognize their value and develop a plan for their restudy and preservation.